1996
DOI: 10.5465/ambpp.1996.4978713
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Timing and Firm Capabilities on the Amount of Capital Raised in an Initial Public Offering: Evidence From the Biotechnology Industry.

Abstract: This paper develops a model of the total level of capital raised by biotech IPOs based on the timing of the offering and the scientific capabilities of the firm. The results indicate a positive relationship between the amount of capital raised by an IPO and the timing of the offering and the scientific capabilities of the firm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
222
4
9

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(243 citation statements)
references
References 2 publications
7
222
4
9
Order By: Relevance
“…Another way of establishing credibility for investment is via the scientific publication records of the biotechnology firm's scientific team (Deeds et al, 1997). In NewPharma, for example, those involved believed publication in a reputable scientific journal was crucial for public validation.…”
Section: Integrative Capabilitiesmentioning
confidence: 99%
“…Another way of establishing credibility for investment is via the scientific publication records of the biotechnology firm's scientific team (Deeds et al, 1997). In NewPharma, for example, those involved believed publication in a reputable scientific journal was crucial for public validation.…”
Section: Integrative Capabilitiesmentioning
confidence: 99%
“…Other studies have examined the impact of firm-specific capabilities on the amount of capital raised in an IPO. For example, in their research on biotechnology firms, Deeds et al (1997) examined the impact of variables such as the location of the firm, the quality of the research staff, the number of products in development, the number of patents held by the firm, and the firm's prior spending on R&D. Amini (2013) analysed the relevance of spatial proximity to London in explaining the amount of money raised by small British firms at IPO and found that spatial proximity to London does have a significant impact; however, contrary to many other studies, he also found that the impacts of profitability, firm age, and hot-market condition are not significant. This is surprising, because, for example, McConaughy, Dhatt, and suggest that firms that perform well before going public have a better chance of success afterwards.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Another novelty of the article is the use of a new measure of success in raising capital. In previous studies, the proceeds divided by total assets (at the end of the IPO year or at the beginning of the IPO year) (Alti, 2006;Çelik & Akarim, 2013;Kim & Weisbach, 2008) and the nominal value of proceeds (Amini, 2013;Callaghan, Kleiman, & Sahu, 1999;Deeds, Decarolis, & Coombs, 1997;Gulati & Higgins, 2003;Mousa, Wales, & Harper, 2015;Zimmerman, 2008) have been used. Our measure reflects the point of view of issuers and is appropriate to measure their success.…”
Section: Introductionmentioning
confidence: 99%
“…Madhok and Osegowitsch (2000) characterize biotechnology as a global hightechnology industry, requiring companies to internationalize their activities very early in their development due to the inadequacy of home-market demand to sustain the firm's development and growth. Biotechnology companies constitute an appropriate sample population because it is believed that companies specialized in this type of technology rely upon different publics to survive, such as potential investors, R&D, and marketing partners (Baum, Calabrese, and Silverman 2000;Baum and Silverman 2004;Deeds, Decarolis, and Coombs 1997;Priest 1995).…”
Section: Samplementioning
confidence: 99%